Gait characterization for osteoarthritis patients using wearable gait sensors (H-Gait systems) - Tadano, Shigeru; Takeda, Ryo; Sasaki, Keita; Fujisawa, Tadashi; Tohyama, Harukazu (Journal of biomechanics, 2016)
The objective of this work was to investigate the possibilities of using the wearable sensors-based H-Gait system in an actual clinical trial and proposes new gait parameters for characterizing OA gait. Seven H-Gait sensors, consisting of tri-axial inertial sensors, were attached to seven lower limb body segments (pelvis, both thighs, both shanks and both feet). The acceleration and angular velocity data measured were used to estimate three-dimensional kinematic parameters of patients during level walking. Three new parameters were proposed to assess the severity of OA based on the characteristics of these joint center trajectories in addition to conventional gait spatio-temporal parameters. The experiment was conducted on ten subjects with knee OA. The kinematic results obtained (hip, knee and ankle joint angles, joint trajectory in the horizontal and sagittal planes) were compared with those from a reference healthy (control) group. As a result, the angle between the right and left knee trajectories along with that of the ankle joint trajectories were almost twice as large (21.3° vs. 11.6° and 14.9° vs. 7.8°) compared to those of the healthy subjects. In conclusion, it was found that the ankle joints during stance abduct less to avoid adduction at the knee as the severity of OA increases and lead to more acute angles (less parallel) between the right and left knee/ankle joints in the horizontal plane. This method was capable to provide quantitative information about the gait of OA patients and has the advantage to allow for out-of-laboratory monitoring.